Chemical Characteristics and NaCl Component Behavior of Biochar Derived from the Salty Food Waste by Water Flushing - Ye-Eun Lee; Jun-Ho Jo; I-Tae Kim; Yeong-Seok Yoo (Energies, 2017)
Biochar is the product of the pyrolysis of organic materials in a reduced state. In recent years, biochar has received attention due to its applicability to organic waste management, thereby leading to active research on biochar. However, there have been few studies using food waste. In particular, the most significant difference between food waste and other organic waste is the high salinity of food waste. Therefore, in this paper, we compare the chemical characteristics of biochar produced using food waste containing low- and high-concentration salt and biochar flushed with water to remove the concentrated salt. In addition, we clarify the salt component behavior of biochar. Peak analysis of XRD confirms that it is difficult to find salt crystals in flushed char since salt remains in the form of crystals when salty food waste is pyrolyzed washed away after water flushing. In addition, the Cl content significantly decreased to 1–2% after flushing, similar to that of Cl content in the standard, non-salted food waste char. On the other hand, a significant amount of Na was found in pyrolyzed char even after flushing resulting from a phenomenon in which salt is dissolved in water while flushing and Na ions are adsorbed. FT-IR analysis showed that salt in waste affects the binding of aromatic carbons to compounds in the pyrolysis process. The NMR spectroscopy demonstrated that the aromatic carbon content, which indicates the stability of biochar, is not influenced by the salt content and increases with increasing pyrolysis temperature.